"Seeing" the social roles of brands: How physical positioning influences brand evaluation1. Issue 4 (16th March 2013) - Huang, Xun (Irene); Li, Xiuping; Zhang, Meng
Abstract: This paper investigates when the brand is promoting a specific social role (as a friend or as a leader), whether the physical position of a brand image in relation to the customer's image influences brand evaluations. Two studies reveal that the match between the promoted social role and the visual representations of the brand and customer in the ad layout improves evaluations. When the brand is promoted as a friend to its customers, consumers evaluate it more positively if the image of the brand is located horizontally and near to the image of the customer. However, when the brand is promoted as a leader to its customers, consumers evaluate it more positively if the image of the brand is located above and far from the image of the customer.